2020
DOI: 10.1039/d0ra07710k
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of coumarin and its analogs on insulin fibrillation /cytotoxicity is depend on oligomerization states of the protein

Abstract: The effect of the applied compounds on insulin fibrillation at two pHs. By and large, the compounds through changing the oligomerization states and altering structure integrity of insulin can govern the fibrillation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“… 17 Some coumarinoids show inhibition of insulin fibrillation. 18 Some coumarin hybrid molecules are also be designed as a multi-targeting agent to stop the fibrillation process in neurodegenerative disorders. 19 All these facts encourage us to investigate some polyphenolic coumarinoids as anti-fibrillating agents.…”
Section: Introductionmentioning
confidence: 99%
“… 17 Some coumarinoids show inhibition of insulin fibrillation. 18 Some coumarin hybrid molecules are also be designed as a multi-targeting agent to stop the fibrillation process in neurodegenerative disorders. 19 All these facts encourage us to investigate some polyphenolic coumarinoids as anti-fibrillating agents.…”
Section: Introductionmentioning
confidence: 99%
“…This assay determines the protective role of compounds in cysteine residues. By masking disulfide bonds, the probability of their reduction would decrease and their resistance against DTT reducing agent would increase . The results of the measurements made in the present research are presented in Figure A.…”
Section: Resultsmentioning
confidence: 99%
“…According to the content of each well, a suitable blank sample was prepared and considering 100% viability for the negative control sample, the percentage of cell viability in each well was displayed. All the experiments were repeated for five times. , …”
Section: Methodsmentioning
confidence: 99%
“…[14][15][16] Moreover, insulin brils can be formed in vitro under certain destabilizing conditions, including evaluated temperature, low pH, and increased ionic strength, which has been a formidable challenge to long-distance shipping and long-term storage of insulin. 17,18 Small-molecule inhibitors have been widely investigated to inhibit protein amyloid, such as b-cyclodextrin, 19 phenolic compounds, 20,21 and molecular tweezer. 22 Several studies have suggested that polyphenolic compounds reduce the risk of several degenerative diseases and exhibit in vitro inhibitory effects on amyloid formation, such as curcuminoids, resveratrol, catechin, (À)-epigallocatechin-3-gallate (EGCG) and soy isoavones.…”
Section: Introductionmentioning
confidence: 99%
“…Small-molecule inhibitors have been widely investigated to inhibit protein amyloid, such as β-cyclodextrin, 19 phenolic compounds, 20,21 and molecular tweezer. 22 Several studies have suggested that polyphenolic compounds reduce the risk of several degenerative diseases and exhibit in vitro inhibitory effects on amyloid formation, such as curcuminoids, resveratrol, catechin, (−)-epigallocatechin-3-gallate (EGCG) and soy isoflavones.…”
Section: Introductionmentioning
confidence: 99%